Dark tetrad personality traits also play a role in bullying victimization - Pineda, David; Rico-Bordera, Pilar; Martínez-Martínez, Ana; Galán, Manuel; Piqueras, José A. (Frontiers in Psychology, 2022)
Bullying refers to physical and/or psychological mistreatment or abuse by one individual or group towards another individual. Bullying is widespread in our society that carries considerable negative consequences. This phenomenon is caused by multiple factors, which include personality. Much more attention has been paid to the study of the negative personality traits of the perpetrators than of the victims. Several studies have examined the relationship between these traits —the Dark Triad or Dark Tetrad— and being a victim of bullying (or mobbing) in adults, especially in the workplace. However, only two studies have been located that have studied these relationships in adolescents. Therefore, the aim of this study was to analyze the relationship between being a victim of bullying and the Dark Tetrad traits, delving into the specific contribution of Machiavellianism, narcissism, psychopathy, and sadism in being victims of bullying in Spanish adolescents. A cross-sectional study was carried out in administering the Short Dark Triad, the Assessment of Sadistic Personality, and the Peer Bullying Questionnaire to 393 adolescents aged 12-18 years (M = 14.18; SD = 2.52; 53.7% male). The Dark Tetrad traits predicted the victimization variables in the seven models analyzed, with the verbal abuse model being the model with the largest contribution. Of the four dark traits, sadism stands out as the trait with the highest specific contribution. Our results, although not implying a causal relationship, indicate that those people with high scores in the Dark Tetrad traits, tend to be more victimized by bullying. Knowing the personality traits of the bullying perpetrators and their victims, practitioners will have a more complete picture of the personality variables that play a role in the prevention of bullying and its associated victimization.